Sudden Sensorineural Hearing Loss and Polymorphisms in Iron Homeostasis Genes: New Insights from a Case-Control Study. (18th February 2015) - Castiglione, Alessandro; Ciorba, Andrea; Aimoni, Claudia; Orioli, Elisa; Zeri, Giulia; Vigliano, Marco; Gemmati, Donato
Abstract : Background . Even if various pathophysiological events have been proposed as explanations, the putative cause of sudden hearing loss remains unclear. Objectives . To investigate and to reveal associations (if any) between the main iron-related gene variants and idiopathic sudden sensorineural hearing loss. Study Design . Case-control study. Materials and Methods . A total of 200 sudden sensorineural hearing loss patients (median age 63.65 years; range 10–92) were compared with 400 healthy control subjects. The following genetic variants were investigated: the polymorphism c.−8CG in the promoter of the ferroportin gene (FPN1; SLC40A1 ), the two isoforms C1 and C2 (p.P570S) of the transferrin protein ( TF ), the amino acidic substitutions p.H63D and p.C282Y in the hereditary hemochromatosis protein ( HFE ), and the polymorphism c.–582AG in the promoter of the HEPC gene, which encodes the protein hepcidin (HAMP). Results . The homozygous genotype c.−8GG of the SLC40A1 gene revealed an OR for ISSNHL risk of 4.27 (CI 95%, 2.65–6.89;P = 0.001 ), being overrepresented among cases. Conclusions . Our study indicates that the homozygous genotype FPN1 −8GG was significantly associated with increased risk of developing sudden hearing loss. These findings suggest new research should be conducted in the field of iron homeostasis in the inner ear.